BUDAYA LOKAL VERSUS BUDAYA GLOBAL - Maimun Fuadi (JURNAL AT-TURAS, 2014)
Najm al-Din al-Thufi al-Hanbali is a smart, intelligent, productive and brave Islamic Scholars. He was considered as controversial person among his colleagues, because of his views on mashlahah are different from the other scholars of Usul -Fiqh in general. He said that the most important sources of Islamic law are the texts (Al-Quran and Al-Sunnah ). It is no problem if both are relevant with mashlahah. However, if they contradict the mashlahah, the solutions that can be taken is prioritizing mashlahah of texts by specification(takhsis), not eliminating texts . At this point Thufi’s thought is considered as controversy. This article will attempt to examine this controversy using argumentative and philosophical approach to be able to point it objectively not tendentiously.